SWOT ANALYSIS OF DIGITAL MARKETING AT MSMEs KING SEMPOL JEMBER - Mohammad Fikri Yusrizal; Fitri Ayu Suryani; Febrina Gerhani (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to identify the strengths, weaknesses, opportunities, and threats (SWOT) associated with the implementation of digital marketing in MSME King Sempol in Jember, as well as to formulate appropriate digital marketing strategies to optimize the utilization of social media platforms. The research employs a SWOT analysis approach to systematically evaluate internal and external factors affecting the business. The findings indicate that the primary strengths of MSME King Sempol include its distinctive product taste, affordable pricing, strategic business location, availability of official social media accounts, and the use of preservative-free raw materials. However, several weaknesses were identified, such as the product’s limited shelf life (only three days), unattractive and inconsistent social media content, the absence of dedicated social media management staff, limited digital marketing knowledge, and unscheduled, unstructured posting practices. In terms of external factors, opportunities include the potential use of influencer testimonials, a large and continuously growing social media user base, increased purchasing power during new student admissions, the high virality of culinary content online, and the expansion of a loyal customer base. Meanwhile, threats consist of similar competitors in the same sales area, rising raw material costs, intense competition in online culinary content, rapidly changing viral food trends, and unstable internet connectivity. The SWOT matrix analysis positions MSME King Sempol in Quadrant I, indicating an aggressive (growth-oriented) strategy. Accordingly, the recommended strategy is the SO (Strength–Opportunity) strategy, which emphasizes leveraging internal strengths to capitalize on external opportunities. Proposed strategies include collaborating with local influencers to enhance brand visibility, consistently promoting products through Instagram and TikTok, offering promotional discounts, creating visually appealing and engaging digital content, and sharing customer testimonials to build trust and strengthen audience engagement. Keywords: Digital Marketing; MSMEs; SWOT